2008
DOI: 10.1038/oby.2008.216
|View full text |Cite
|
Sign up to set email alerts
|

Association Between BMI and Metabolic Syndrome and Adenomatous Colonic Polyps in Korean Men

Abstract: Obesity and insulin resistance are associated with the risk of colon cancer. Adenomatous colonic polyps are precancerous lesions of colon cancer. We investigated whether BMI and the metabolic syndrome are associated with the presence of adenomatous colonic polyps in Korean men. Anthropometric measurements, metabolic risk factors, and colonoscopic pathologic findings were assessed in 1,898 men who underwent routine colonoscopy at the Health Promotion Center of Asan Medical Center in 2005. The modified National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 35 publications
10
48
2
3
Order By: Relevance
“…In addition, MetS-component numbers were reported in many convincing studies that closely linked them with damaged conditions of the whole human body: impaired cardiovascular conditions [32,33] , cognitive impairment [34] , and colon polyps [35] . Shift work is associated with the premature aging process [36] , and as demonstrated in our analyses (Table 4 and Figure 1), the e-ATL-plus-pRSW workers had significantly increased numbers of MetScomponents in the end of follow-up.…”
Section: Increasing Mets-component Numbers and Development Of Mets Ammentioning
confidence: 99%
“…In addition, MetS-component numbers were reported in many convincing studies that closely linked them with damaged conditions of the whole human body: impaired cardiovascular conditions [32,33] , cognitive impairment [34] , and colon polyps [35] . Shift work is associated with the premature aging process [36] , and as demonstrated in our analyses (Table 4 and Figure 1), the e-ATL-plus-pRSW workers had significantly increased numbers of MetScomponents in the end of follow-up.…”
Section: Increasing Mets-component Numbers and Development Of Mets Ammentioning
confidence: 99%
“…As for the association between obesity and colorectal adenomatous polyps, even though most epidemiological studies including cross-sectional studies, case-control studies, and cohort studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) reported a positive association, several studies (20)(21)(22)(23)(24)(25) showed no significant association. Moreover, the findings on the relationship between obesity and the risk of colorectal polyps were inconsistent by gender (12,14,15,19) or types of body measures for obesity such as BMI and WC (12,19).…”
Section: Introductionmentioning
confidence: 99%
“…İnsülin normal mukozada apoptozu azaltarak kolorektal adenomdan kanser gelişme zincirini uyarabilir [1,5,8] [1,7,18].…”
Section: İnsülin Direnci Ve Insülin Büyüme Faktörü Bağlayıcı Proteinunclassified
“…70 yaş üzerinde ise prevalans kadınlarda %70, erkeklerde %49 bulunmuştur [4]. MS, santral obezite, bozulmuş glukoz toleransı, HT, hipertrigliseridemi, yüksek yoğunluklu lipoprotein kolesterol (HDL-K) düşüklüğü ile karekterizedir [1,3,5]. İnsülin direnci, dolaşımda yüksek insülin düzeyi ile karakterize prediyabetik bir durumdur.…”
Section: Introductionunclassified
See 1 more Smart Citation